Discovery of 5-(methylthio)pyrimidine derivatives as L858R/T790M mutant selective epidermal growth factor receptor (EGFR) inhibitors. Issue 12 (15th June 2016) - Xiao, Qiang; Qu, Rong; Gao, Dingding; Yan, Qi; Tong, Linjiang; Zhang, Wei; Ding, Jian; Xie, Hua; Li, Yingxia
Graphical abstract: Abstract: To overcome the drug-resistance of first generation EGFR inhibitors and the nonselective toxicities of second generation inhibitors among NSCLC patients, a series of 5-(methylthio)pyrimidine derivatives were discovered as novel EGFR inhibitors, which harbored not only potent enzymatic and antiproliferative activities against EGFR L858R/T790M mutants, but good selectivity over wide-type form of the receptor. This goal was achieved by employing structure-based drug design and traditional optimization strategies, based on WZ4002 and CO1686. These derivatives inhibited the enzymatic activity of EGFR L858R/T790M mutants with IC50 values in subnanomolar ranges, while exhibiting hundreds of fold less potency on EGFR WT . These compounds also strongly inhibited the proliferation of H1975 non-small cell lung cancer cells bearing EGFR L858R/T790M, while being significantly less toxic to A431 human epithelial carcinoma cells with overexpressed EGFR WT . The EGFR kinase inhibitory and antiproliferative activities were further validated by Western blot analysis for activation of EGFR and the downstream signaling in cancer cells.